Assessing the physicochemical and functional properties of cassava and wheat flour - Nur Fathin Shamirah, Daud; Farhan, Mohd Said; Fatmawati, Adam (AIP, 2026)
Cassava presents a wide range of industrial applications, creating opportunities for more profitable markets. Therefore, extensive research on native cassava for the food industry is necessary as a potential strategy to drive improvements in the value chain. Thus, a comparative analysis of native cassava flour compared to commercial cassava flour and wheat flour was studied, especially on the physicochemical and functional properties. The properties of cassava and wheat were investigated using X-ray diffraction (XRD), syneresis, swelling power (SP), and water solubility index (WSI). The results showed that the SP and WSI of native cassava flour were comparable to commercial wheat flour, with values of 16.99 g/g and 5.61% for native cassava flour and 13.13 g/g and 7.43% for wheat flour, respectively. The A-type starch crystallinity, SP, and WSI observed in native cassava flour indicated that it could replace wheat in food product development.